PEMIKIRAN PERENIALISME ST. THOMAS AQUINAS TERHADAP DUNIA PENDIDIKAN ISLAM - Maharani Maharani (ISLAMIKA, 2025)
In the modern era, humans have begun to lose their essence and they prioritize their own existence. Thomas Aquinas was a steadfast philosopher and theologian. When western scientists fiercely opposed his philosophical theorities, he remained firm by maintaining principles that recognized God?s power which is not the same as that of His creatures. The method applied in this research is library research (library search, where in collecting data most of it is obtained from literature and references, both from books, scientific journals, electronic books (ebooks), and the internet related to the research theme. Perennialism can be a solution to return to past civilizations which are considered ideal in line with Plato?s philosophy of idealism. The Qur?n is a source of solutions to various kinds of human moral crises so that educators play a role in realizing perennialism through a character education approach.